Development of Traffic Light Control System for Educational Purpose using Motorola 68HC11 Microcontroller - Adam, Asrul; York Leong, Liew; Zainal Abidin, Amar Faiz; Kadiran, Kamaru Adzha; Rifin, Rozi; Hasim, Saipol Hadi (Journal of Advanced Research in Applied Mechanics, 2020)
Nowadays, traffic congestion has caused many problems such as wastage of time and environment pollution. This paper aims to develop a traffic control system for education level using Motorola 68HC11 microcontroller where the system will try to reduce the possibilities of congestion that caused by the traffic light. In addition, the system will also consider the needs of pedestrian road crossing. This system will be designed based on the sequence-based method where the traffic light sequence and timing are controlled by different receipt that selected by the program under different traffic situations. By implementing the developed traffic control system, the system is able to shorten the traffic waiting period and ensure the safety of the road user at the 4 lanes junction. Switches that represent the detector sensors will be installed at a distance around the traffic displays to monitor the status on each of the lane. When the sensor is blocked by a vehicle or a passenger at the specific location, it will be triggered and inform the microcontroller to change the timing of the green light at the respective lane.